AUDIT ON THE UTILIZATION OF ABDOMINAL ULTRASOUND IN DENGUE FEVER DIAGNOSIS: A TWO-CYCLE STUDY - AFZAL, U; NADEEM, J; AHMAD, S; FARAZ, A; ASHFAQ, F (Biological and Clinical Sciences Research Journal, 2024)
Dengue fever is a viral infection transmitted by mosquitoes, prevalent in tropical and subtropical regions, including Pakistan. It can range from mild illness to severe hemorrhagic fever, and timely diagnosis is crucial for effective management, particularly during outbreaks. Abdominal ultrasound is an important tool for diagnosing dengue fever, as it can identify critical signs indicative of severe dengue. Objective: This audit assesses compliance with hospital guidelines for using abdominal ultrasound in suspected dengue cases before and after an intervention to improve adherence. Methods: A prospective audit was conducted in two cycles, with the first covering September 1, 2021, to October 1, 2021, at Akhtar Saeed Trust Hospital, Lahore. An intervention was implemented, including educational sessions and dissemination of informational materials to healthcare providers. The second audit cycle followed the same methodology to evaluate the impact of these interventions. Results: The first cycle revealed that out of 80 patients admitted with confirmed dengue fever, only ten patients (12.5%) underwent an abdominal ultrasound. All ultrasound reports included findings specific to dengue fever. The second post-intervention cycle showed significant improvement, with 60 patients (75%) receiving an ultrasound and all reports documenting relevant findings. Conclusion: The audit highlighted a substantial initial gap in using abdominal ultrasound for dengue fever diagnosis. Post-intervention, there was a notable improvement in compliance, demonstrating the effectiveness of educational initiatives. However, continued efforts are needed to achieve full adherence to guidelines.